Not dominance but the loss of binocularity determines the success of monovision - Veerle Van Severen; Sven Van Laere; Marcel Ten Tusscher (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2021)
Purpose: To determine whether ocular dominance strength influences success of monovision  Design: Single-center, prospective, double blind crossover. Subjects received contact lenses with reading addition added to the left eye in the first trial period and to the right eye in the second period so that the type of monovision was randomized and blinded for the test subject and the investigator. Methods: 17 presbyopic subjects, aged 50-65, received conventional and crossed monovision, each for 2 weeks. Satisfaction, stereopsis (TNO, Titmus) and Snellen visual acuity were measured. Ocular dominance was examined according to Haidinger and +1D test.  Results: Pearson correlation coefficient between strength of ocular dominance and subject satisfaction was ρ=0.088 for the conventional and ρ=0.000 for the crossed group. 93% of subjects were most satisfied with the type of monovision that yielded the highest Titmus score. For the TNO test this was only 64%. A statistical significant interaction effect was shown for this relationship (ρ=0.019). Conclusion: A significant correlation between dominance strength, refraction error and satisfaction could not be found. However, we observed that the highest stereopsis score according to the Titmus test was more likely to yield a higher satisfaction when comparing conventional and crossed monovision. When a physician opts for monovision correction, the Titmus test can be performed with test spectacles or contact lenses to decide which eye should be corrected for distance vision. The choice should be in favor of the correction that yields the best Titmus score.